2002
DOI: 10.1556/aling.49.2002.3-4.6
|View full text |Cite
|
Sign up to set email alerts
|

The temporal organisation of speech in monolingual and bilingual children

Abstract: Research on the temporal organisation of speech with respect to age is extremely important as it may provide empirical confirmation for the various models of speech production. With the advancement of age, speech motor control becomes more secure, and so the child gradually approaches the level of articulation and speech tempo typical of adults. There have been numerous works published on the temporal relations of English-speaking, normally developing children; however, the relevant literature still lacks data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…She found a slower speech rate for bilingual compared to monolingual children at both age groups and in both languages. The results of both Trofimovich and Baker (2007) and Menyhárt (2002) are consistent with a large body of work on L2 adult speakers, which shows a gradual development of L2 articulation rate over time (Lennon, 1990; Munro & Derwing, 1995; Riggenbach, 1991).…”
Section: Development Of Articulation Ratesupporting
confidence: 85%
See 1 more Smart Citation
“…She found a slower speech rate for bilingual compared to monolingual children at both age groups and in both languages. The results of both Trofimovich and Baker (2007) and Menyhárt (2002) are consistent with a large body of work on L2 adult speakers, which shows a gradual development of L2 articulation rate over time (Lennon, 1990; Munro & Derwing, 1995; Riggenbach, 1991).…”
Section: Development Of Articulation Ratesupporting
confidence: 85%
“…Menyhárt (2002) also examined the speech rate of children who were born into bilingual environments. She compared Hungarian-Bulgarian bilingual children either aged 9–10 or 12–13 year olds to monolingual age-matched peers.…”
Section: Development Of Articulation Ratementioning
confidence: 99%
“…In fact, compared to a sizeable body of research on the development of speech rate in monolingual children (e.g., Smith, Kenney, & Hussain, 1996), literature on speech rate in child L2 learners (or bilingual children) is small. To our knowledge, the only study examining the development of speech rate in child L2 learners is Menyhárt's (2002) investigation of temporal characteristics of speech in Hungarian and Bulgarian monolingual and bilingual 9-to 10-and 12-to 13-year-olds exposed to their L2 from early infancy. Menyhárt (2002) found that bilingual children produced L2 speech at a slower rate than aged-matched monolingual children, and that older children produced L2 speech at a faster rate than younger children.…”
Section: Speech Ratementioning
confidence: 99%
“…To our knowledge, the only study examining the development of speech rate in child L2 learners is Menyhárt's (2002) investigation of temporal characteristics of speech in Hungarian and Bulgarian monolingual and bilingual 9-to 10-and 12-to 13-year-olds exposed to their L2 from early infancy. Menyhárt (2002) found that bilingual children produced L2 speech at a slower rate than aged-matched monolingual children, and that older children produced L2 speech at a faster rate than younger children. Although revealing, these findings likely characterize bilingual children's nearly simultaneous acquisition of two languages.…”
Section: Speech Ratementioning
confidence: 99%
See 1 more Smart Citation